Sphenopalatine Ganglion Stimulation to Augment Cerebral Blood Flow: A Randomized, Sham-Controlled Trial. Issue 8 (August 2019) - Bornstein, Natan M.; Saver, Jeffrey L.; Diener, Hans-Christoph; Gorelick, Philip B.; Shuaib, Ashfaq; Solberg, Yoram; Devlin, Thomas; Leung, Thomas; Molina, Carlos A.
Abstract : Background and Purpose—: Many patients with acute ischemic stroke are not eligible for thrombolysis or mechanical reperfusion therapies due to contraindications, inaccessible vascular occlusions, late presentation, or large infarct core. Sphenopalatine ganglion (SPG) stimulation to enhance collateral flow and stabilize the blood-brain barrier offers an alternative, potentially more widely deliverable, therapy. Methods—: In a randomized, sham-controlled, double-masked trial at 41 centers in 7 countries, patients with anterior circulation ischemic stroke not treated with reperfusion therapies within 24 hours of onset were randomly allocated to active SPG stimulation or sham control. The primary efficacy outcome was improvement beyond expectations on the modified Rankin Scale of global disability at 90 days (sliding dichotomy), assessed in the modified intention-to-treat population. The initial planned sample size was 660 patients, but the trial was stopped early when technical improvements in device placement occurred, so that analysis of accumulated experience could be conducted to inform a successor trial. Results—: Among 303 enrolled patients, 253 received at least one active SPG or sham stimulation, constituting the modified intention-to-treat population (153 SPG stimulation and 100 sham control). Age was median 73 years (interquartile range, 64–79), 52.6% were female, deficit severity on the National Institutes of Health Stroke Scale was median 11 (interquartile range, 9–15), and time from last known well median 18.6 hours (interquartile range, 14.5–22.5). For the primary outcome, improved 3-month disability beyond expectations, rates in the SPG versus sham treatment groups were 49.7% versus 40.0%; odds ratio, 1.48 (95% CI, 0.89–2.47); P =0.13. A significant treatment interaction with stroke location (cortical versus noncortical) was noted, P =0.04. In the 87 patients with confirmed cortical involvement, rates of improvement beyond expectations were 50.0% versus 27.0%; odds ratio, 2.70 (95% CI, 1.08–6.73); P =0.03. Similar response patterns were observed for all prespecified secondary efficacy outcomes. No differences in mortality or serious adverse event safety end points were observed. Conclusions—: SPG stimulation within 24 hours of onset is safe in acute ischemic stroke. SPG stimulation was not shown to statistically significantly improve 3-month disability above expectations, though favorable outcomes were nominally higher with SPG stimulation. Beneficial effects may distinctively be conferred in patients with confirmed cortical involvement. The results of this study need to be confirmed in a larger pivotal study. Clinical Trial Registration—: URL: https://www.clinicaltrials.gov . Unique identifier: NCT03767192. Abstract : Supplemental Digital Content is available in the text.